Late acute myopia syndrome induced by combination of sulfonamide drugs - Kozner, Pavel; Simonova, Katarina; Brozek, Bretislav; Singh, Kuldev (Journal of glaucoma, 2014)
We present a case of late acute myopia syndrome following discontinuation of treatment with a combination of sulphonamide drugs. To the best of our knowledge, this is the first reported case with such a presentation, and suggests that the pathophysiological basis for the acute myopia syndrome is a rapid decrease in serum carbonic anhydrase inhibitors levels which may lead to a rebound increase in the production of aqueous humor and accumulation of suprachoroidal fluid. It is further postulated that there may be a cumulative effect of sulphonamide drug use on carbonic anhydrase activity in the ciliary body epithelium of susceptible individuals.
Keywords: Topiramate; kombinovaná farmakoterapie; kombinace léků trimethoprim a sulfamethoxazol; myopie; lidé; ženské pohlaví; Acute Disease; Anti-Infective Agents; Fructose; Trimethoprim, Sulfamethoxazole Drug Combination; Female; akutní nemoc; nitrooční tlak; Anticonvulsants; Drug Therapy, Combination; Intraocular Pressure; antiinfekční látky; topiramat; migréna; Adult; Myopia; Migraine Disorders; faryngitida; Humans; dospělí; fruktosa; Pharyngitis; antikonvulziva